Investigating and developing beginner learners' decoding proficiency in second language French: an evaluation of two programmes of instruction - Woore, R (2011)
Second language (L2) decoding – the sub-lexical process of mapping the graphemes of an alphabetic writing system onto the phonemes they represent – is argued to underpin various aspects of L2 learning, particularly vocabulary acquisition. Recently, second language acquisition research has shown increased interest in decoding, consistently finding evidence for L1-to-L2 transfer effects on learners’ processing mechanisms and outcomes. Correspondingly, studies conducted in Modern Foreign Language (MFL) classrooms in English secondary schools – an under-researched context – have found that beginner learners of French tend to (a) pronounce L2 words according to English decoding conventions and (b) make poor progress in this aspect of L2 learning. Recent official guidance for MFL teachers has addressed this problem by advocating an explicit focus on decoding, but there is a lack of convincing evidence (both in the MFL context and more widely) that explicit L2 decoding instruction can be effective. The current study therefore trialled two programmes of French decoding instruction for beginner MFL learners, delivered in ten- to fifteen-minute segments over around thirty lessons. Three intact secondary school classes followed a phonics-based approach; three classes from another school followed a programme in which learners were encouraged to derive the pronunciations of French graphemes from ‘source words’ in a memorized poem; and six classes in two other schools received no explicit decoding instruction. Participants (N=186) completed pre- and post-tests of French decoding; a sub-sample (N=15) also completed task-based self-report interviews. The two intervention groups made significantly more progress than the comparison group in terms of the number of graphemes pronounced ‘acceptably’, although the magnitude of the difference between the groups was small. Compared to the comparison group, the two intervention groups also appeared to show different and more extensive patterns of change in their realizations of individual graphemes, even where their pronunciations were still not ‘acceptable’. Finally, self-report data generally revealed little change in participants’ strategic reasoning, either in the intervention or comparison group. Together, these findings suggest that explicit instruction can improve beginner learners’ proficiency in decoding L2 French, but that their progress may follow a longer and more complex trajectory than simply moving directly from ‘incorrect’ to ‘correct’ forms. Further research is required to assess the effects (if any) of a given improvement in decoding proficiency on other language-learning outcomes; and to design and evaluate alternative programmes of instruction.